2005
DOI: 10.1099/ijs.0.63426-0
|View full text |Cite
|
Sign up to set email alerts
|

Petrimonas sulfuriphila gen. nov., sp. nov., a mesophilic fermentative bacterium isolated from a biodegraded oil reservoir

Abstract: A mesophilic, anaerobic, fermentative bacterium, strain BN3T, was isolated from a producing well of a biodegraded oil reservoir in Canada. Cells were Gram-negative, non-motile rods that did not form spores. The temperature range for growth was 15–40 °C, with optimum growth at 37–40 °C. The strain grew with up 4 % NaCl, with optimum growth in the absence of NaCl. Tryptone was required for growth. Yeast extract and elemental sulfur stimulated growth. Growth was also enhanced during fermentation of glucose, arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(113 citation statements)
references
References 73 publications
2
107
0
4
Order By: Relevance
“…6C). P. sulfuriphila, which was related to OTU 1, is a strictly anaerobic bacterium that ferments carbohydrates and organic acids (11). Many bacteria identified as being closely related to Bacteroidetes OTUs from this study, like Proteiniphilum acetatigenes, P. sulfuriphila, and A. imshenetskii, were also found previously in other biogas reactors (18,19).…”
Section: Discussionmentioning
confidence: 57%
“…6C). P. sulfuriphila, which was related to OTU 1, is a strictly anaerobic bacterium that ferments carbohydrates and organic acids (11). Many bacteria identified as being closely related to Bacteroidetes OTUs from this study, like Proteiniphilum acetatigenes, P. sulfuriphila, and A. imshenetskii, were also found previously in other biogas reactors (18,19).…”
Section: Discussionmentioning
confidence: 57%
“…Strain ING2-E5B T showed weak growth on both peptone and tryptone and on a mixture of the two. A requirement for tryptone, as described for Petrimonas sulfuriphila BN3 T (Grabowski et al, 2005), was not observed for the novel strains. For Proteiniphilum acetatigenes TB107 T , it was reported that the strain was not able to use any of a variety of tested carbohydrates (Chen & Dong, 2005); however, in our experiments, all tested mono-and disaccharides (arabinose, cellobiose, fructose, galactose, glucose, lactose, maltose, mannose, rhamnose, sucrose and trehalose) supported cell growth of Proteiniphilum acetatigenes DSM 18083…”
Section: S Hahnke and Othersmentioning
confidence: 73%
“…The Lactobacillus species produce lactic acid as the major end product in carbohydrate fermentation (28). Petrimonas is reported to produce acetic acid, hydrogen, and CO 2 during glucose fermentation (29). Sedimentibacter ferments amino acids and glycine to ethanol or to acetic acid and butyric acid (30,31).…”
Section: Discussionmentioning
confidence: 99%